A Multi-agent Supply Chain Information Coordination Mode Based on Cloud Computing - Wuxue Jiang; Jing Zhang; Junhuai Li (Institute of Advanced Engineering and Science, 2013)
In order to improve the high efficiency and security of supply chain information coordination under cloud computing environment, this paper proposes a supply chain information coordination mode based on cloud computing. This mode has two basic statuses which are online status and offline status. At the online status, cloud computing center is responsible for coordinating the whole supply chain information. At the offline status, information exchange can be realized among different nodes by using the pre-backup supply chain information and network address of other nodes. This coordination mode coordinates the whole supply chain information through the cloud computing center at the online status and maximizes the overall benefit. Meanwhile, the offline status effectively avoids the risks to the whole supply chain brought by the overdependence of cloud computing on network and the high information concentration. The two statuses have good customers’ satisfaction and higher order finished rate in supply chain. The simulation experiment based on multi-Agent verifies the effectiveness of this mode in this paper. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3453